2022
DOI: 10.1097/md.0000000000032254
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D supplementation on glycemic status and C-reactive protein levels in type 2 diabetic patients with ischemic heart disease: A protocol for systematic review and meta-analysis

Abstract: Background: Vitamin D might be beneficial in diabetic patients with ischemic heart disease through its favorable effect on metabolic profiles and biomarkers of inflammation and oxidative stress. We performed a protocol for systematic review and metaanalysis to assess whether vitamin D supplementation could improve glucose control and inflammation in type 2 diabetic patients with ischemic heart disease.Methods: The proposed systematic review and meta-analysis will conform to the Preferred Reporting Items for Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The mechanisms involved include elevating the levels of anti-inflammatory cytokines while lowering the levels of proinflammatory cytokines. It is also indicated as a therapeutic option in the management of diabetes mellitus [ 160 , 161 ] and skin diseases [ 162 ]. Cheng et al [ 163 ] conducted a systematic review and randomized control trial and observed that vitamin D can reduce negative emotions.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms involved include elevating the levels of anti-inflammatory cytokines while lowering the levels of proinflammatory cytokines. It is also indicated as a therapeutic option in the management of diabetes mellitus [ 160 , 161 ] and skin diseases [ 162 ]. Cheng et al [ 163 ] conducted a systematic review and randomized control trial and observed that vitamin D can reduce negative emotions.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, there is consensus about the beneficial effect of vitamin D on peripheral artery disease, foot ulceration prevention, and wound healing. Vitamin D plays a vital role on indexes of insulin and lipid profile through its impact on activating insulin receptor expression [6].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the causal relationship between serum levels of carotenoids and CVD prevalence has not been fully understood. Additionally, other dietary or environmental factors (e.g., artificial sweeteners, vitamin D, dietary fiber, and heavy metals) may still have influences on the conclusions even after model adjustment as carotenoids are mainly obtained from fruits and vegetables (41)(42)(43)(44). The limitations of the WQS regression analysis may also affect the conclusions as the all-positive and all-negative dependent variables have the same effects on exposure.…”
Section: Discussionmentioning
confidence: 99%